Atrial Myxoma: An Unusual Cause of Myocardial Infarction - Demir, Mesut (2005)
A 55-year-old woman had an inferior myocardial infarction due to a coronary artery embolus from a large, polypoid, left atrial mass. The mass had an irregular surface and was prolapsing into the mitral valve orifice during diastole. Coronary angiography revealed tumor vascularization next to the right coronary artery. The other coronary arteries were normal. The tumor was removed surgically; pathologic examination confirmed the diagnosis of myxoma. The patient did well after the procedure and was discharged on postoperative day 10.